Need Analysis to Develop a Physics Module Integrated Natural Disaster and Mitigation - Neni Hermita; Eri Afriyani; Naila Fauza (Postgraduate, University of Mataram, 2023)
Physics is the study of phenomena, symptoms and interactions of objects that occur in nature. One of the phenomena that often occurs is natural disasters. Natural disasters are a series of events that occur naturally or non-naturally that can harm humans and anything in nature. Natural disasters can be prevented or reduced by doing mitigation. Mitigation is an effort carried out before a natural disaster occurs which aims to reduce or prevent the occurrence of natural disasters. In learning physics, natural disasters can be analyzed in physics concepts so that a teacher can make natural disaster phenomena a phenomenon that can increase students' knowledge in studying physics. Therefore, teachers need teaching materials that are integrated with natural disasters and mitigation to support learning to convey and analyze the role of physics in natural disaster phenomena and mitigation. The purpose of this study was to describe the teacher's need for the development of an integrated physics module for natural disasters and mitigation as teaching materials in physics learning. This research is qualitative research with the subject of research is physics teacher from several schools in Riau. Data collection was carried out using a non-test method by providing a questionnaire in the form of a google form. The results of the questionnaire show that most teachers need physics teaching materials in the form of an integrated physics module for natural disasters and mitigation.